Pengembangan e-Modul Pembelajaran Berbasis Chemo-Edutainment pada Pokok Bahasan Sistem Periodik Unsur - Dahniar Natalia Sipayung; Jamalum Purba (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2024)
Learning with chemo-edutainment-based e-modules on the subject of the periodic system of this element is expected to improve student learning outcomes. This study aims to: (1) determine the feasibility of chemo-edutainment-based learning e-modules in accordance with BSNP standards, namely content feasibility, presentation feasibility, language feasibility and graphic feasibility; (2) knowing the practicality of e-modules that have been developed through the responses of chemistry teachers and learners. The research method used is Research & Development (R&D) with 4D models (define, design, develop and desseminate) limited to the develop stage. The final product in the form of a flippbook-shaped e-module assisted by Flip PDF Professional was carried out feasibility validation tests and practical tests by 2 chemistry teachers and 31 students. The results of the e-module feasibility percentage in this study are, in the aspect of content feasibility of 93%, presentation feasibility of 95%, language feasibility of 95%, and graphic feasibility of 84%. The results of the practicality test through the response of the chemistry teacher got a result of 97% and the response of students got a result of 97%.